Sociology Program Review Dean's Review: Vandana Kohli (2023)
This is the Dean's response to the Sociology program review conducted between 2021 and 2022. Any issue that emerged during the program review that needs to be addressed at the University level is not included in my summary observations and recommendations. Rather, the Dean's office will work with the appropriate academic support units to address the issues noted by the external reviewers as part of the MOU development and implementation process.The Sociology external reviewers conclude that, at this stage, Sociology should not consider developing a graduate degree in Sociology. Further, they conclude that a degree in Criminology and/or its variant should not be housed under sociology. I too, support, both of these conclusions given that the faculty is not supportive of either of these initiatives.